Neurogenesis in Neurodegenerative Diseases: Role of MFG-E8 - Cheyuo, Cletus; Aziz, Monowar; Wang, Ping (Frontiers in Neuroscience, 2019)
Neurodegenerative diseases are devastating medical conditions with no effective treatments. Restoration of impaired neurogenesis represents a promising therapeutic strategy for neurodegenerative diseases. Milk fat globule-epidermal growth factor-factor VIII (MFG-E8) is a secretory glycoprotein that plays a wide range of cellular functions including phagocytosis of apoptotic cells, anti-inflammation, tissue regeneration and homeostasis. The beneficial role of MFG-E8 has been shown in cerebral ischemia (stroke), neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s disease, and traumatic brain injury (TBI). In stroke, MFG-E8 promotes neural stem cell proliferation and their migration towards the ischemic brain tissues. These novel functions of MFG-E8 are primarily mediated through its receptor αvβ3-integrin. Here we focus on the pivotal role of MFG-E8 in protecting against neuronal diseases by promoting neurogenesis. We also discuss the mechanisms of MFG-E8-mediated neural stem/progenitor cell (NSPC) proliferation and migration, and the potential of MFG-E8 for neural stem cell niche maintenance via angiogenesis. We propose further investigation of the molecular pathways for MFG-E8 signaling in NSPC and effective strategies for MFG-E8 delivery across the blood-brain barrier, which will help develop MFG-E8 as a future drug candidate for the bedside management of neurodegenerative diseases.